Learn iOS App development - Bucanek, James (Apress Imprint: Apress, 2013)
Learn iOS App Development is both a rapid tutorial and a useful reference. You'll quickly get up to speed with Objective-C, Cocoa Touch, and the iOS 7 SDK. It's an all-in-one getting started guide to building your first iPhone or iPad app. You'll learn best practices that ensure your code will be efficient and perform well, earning positive reviews on the iTunes App Store, and driving better search results and more revenue. The iOS 7 SDK offers powerful new features, and this book is the fastest path to mastering them-and the rest of the iOS SDK -for programmers with some experience who are new to iPhone and iPad app development. Many books introduce the iOS SDK, but few explain how to develop apps optimally and soundly. This book teaches both core Objective-C language concepts and how to exploit design patterns and logic with the iOS SDK, based on Objective-C and the Cocoa Touch framework. Why spend months or years discovering the best ways to design and code iPhone and iPad apps when this book will show you how to do things the right way from the start? Get an accelerated treatment of the core fundamentals of Objective-C. Develop your first app using Xcode's advanced interface design tools. Build your first iPhone app using the code that you're given as you walk through this book. Finally, debug and distribute your first app on Apple's iTunes App Store. Learn how to create apps for any model of iPhone, the iPod Touch, the iPad, or build universal apps that run on all of them. After reading this book, you'll be creating professional quality apps, ready to upload to the app store, making you the prestige and the money you seek!